Assessment of the possibility to use the of hot dip galvanizing waste-zinc dust for zinc-rich paints - N. I. Urbanovich; K. A. Baranovsky; E. V. Rozenberg; V. A. Ashuyko (Литьë и металлургия)
The chemical and grain-size analysis of zinc dust – waste of hot – dip zinc plating were made. The research results showed that zinc dust is a dispersed waste with particles of mainly circular shape and sizes from 3 to 200 microns, and in chemical composition it mainly meets the requirements of ISO 3549. The presence of lead in the zinc dust composition, which is slightly higher than the acceptable level will be taken into account in the development of zinc-rich paints compositions. Analysis of the results of sieving of zinc dust showed that it contains particles of size £15 µm, which is about 27% of its fractional composition and which can be recommended for the manufacture of zinc-rich paints.